Guidelines for the inclusion of ADHD learners in the classroom - Stewart, Tracey-Jane (North-West University, 2006)
Although Attention-Deficit/Hyperactivity Disorder (ADHD) is a common disorder amongst school going children, it is often misdiagnosed, misunderstood and mismanaged. This state of affairs does not bode well for the development of the ADHD learner and often leads to long-term impairments in terms of the learner's social and emotional development, academic performance and future vocational success. Therefore, it is essential that teachers fully understand the disorder and know how to optimally accommodate ADHD learners in their classrooms. The aims of the research were as follows: to determine whether a significant difference exists between teachers' ratings of the importance of certain didactic approaches, behaviour management strategies and parental involvement in accommodating ADHD learners in "regular" classrooms on the one hand, and the frequency of teachers' implementation thereof on the other; and to determine how variables such as gender, age, teaching experience and qualifications affect (1) teachers' ratings of the importance of certain didactic approaches, behaviour management strategies and parental involvement for accommodating ADHD learners in "regular" classrooms and (2) the frequency of teachers' implementation thereof. A dual research approach was followed to achieve the aims of the research. First, a literature study was done on ADHD with reference to its aetiology, prevalence, symptoms, co-morbid features and treatment options. The implications of accommodating ADHD learners in "regular" classrooms were discussed against the background of the inclusive educational approach. Second, an empirical investigation was undertaken to determine how important teachers rate various inclusive didactic approaches and strategies and how frequently they implement them. The effect that variables such as gender, age, qualifications and teaching experience could have on teachers' ratings of the importance and frequency of implementation of these inclusive didactic approaches and strategies were also investigated. A structured questionnaire was distributed amongst 115 intermediate phase teachers who are teaching in ex-Model C primary schools in the Klerksdorp and Potchefstroom school districts. The data was statistically analysed and the following conclusions were drawn: Although teachers are aware of the importance of certain didactic approaches, behaviour management strategies and parental involvement for the optimal inclusion of ADHD learners in "regular" classrooms, in practice they do not implement these aspects so frequently. Female teachers rate the implementation of certain didactic approaches, strategies related to teacher behaviour and parental involvement more important for accommodating ADHD learners in their classrooms than their male counterparts, and implement them more frequently than male teachers. In general, variables such as gender, age, teaching experience and qualifications do not significantly affect (1) teachers' ratings of the importance of certain didactic approaches, behaviour management strategies and parental involvement for accommodating ADHD learners in regular classrooms, or (2) the frequency of teachers' implementation thereof. Resulting from the findings of the research, practical guidelines were recommended to enhance the teaching and inclusion of ADHD learners in "regular" classrooms.
Thesis (M.Ed.)--North-West University, Potchefstroom Campus, 2006.
Keywords: ADHD learners; Inclusion; Guidelines